The European Financial Market Stress Index - Corbet, Shaen (International Journal of Economics and Financial Issues, 2014)
This research constructs and develops a financial stress index based on European financial markets. The integration of numerous sovereign states has created difficulty identifying stress in any one single financial component, but incorporating twenty-three headline European stress indicators across equities, bonds and currencies, in terms of both spreads and levels offer substantial explanatory benefits. The incorporation of a logistical framework specifically analysing the levels, volatility and co-movement of the included standardised series enables the creation of an index that adequately represents financial market stress in European. Using periods of pre-defined crisis in a logistic regression framework also aids the development of the index. The results provide evidence that the European-specific sovereign crises from 2010 to present, with particular emphasis on the mid-2011 period, have significantly over-shadowed any event that the financially-integrated Europe has previously experienced. Keywords: European financial crisis; financial market stress indicator; liquidity; stock markets. JEL Classifications: G01; G15